Phytochemical Composition of Polyphenolic Compounds of Achillea Collina (Becker ex Rchb.) - Duyun, I. F.; Mazulin, O. V.; Smoilovska, G. P.; Mazulin, G. V.; Дуюн, Ірина Федорівна; Мазулін, Олександр Владиленович; Смойловська, Галина Павлівна; Мазулін, Георгій Владиленович (Izdevnieciba “Baltija Publishing”, 2017)
Achillea L. genus include about 150 species and there is widely distributed on Europe, Asia, North Africa, North America. Up to 30 Achillea species grow in Ukraine. Achillea millefolium L. and Achillea collina (Becker ex Rchb.) (syn. Achillea millefolium ssp. collina (Becker ex Rchb.) is perspective for use in official medicine. A scheme for analysis of etanolic and methanolic extracts of Achillea collina (Becker ex rchb.) herbal raw material including of flavonoids and hydroxycinnamic acids by TLC and HPLC and their determination by high-performance liquid chromatography was proposed. The aim of the research was study the accumulation, qualitative and quantitative content of polyphenolic compounds in flowers and leaves of Achillea collina (Becker ex Rchb.). The 12 flavonoids are identified in Achillea collina (Becker ex Rchb.) flowers 1.303±0.110% and leaves (0.862±0.091%). Contents of the apigenin-7.4’-bi-O-glucoside (0.304±0.004%), luteolin-7.3’-bi-glucoside (0.300±0.005%) and luteolin-7-O-glucoside (0.154±0.004%) were significant and quercitin 3-0-rutinosid yielded the lowest amount (0.019±0.002%) in study of flowers Achillea collina (Becker ex Rchb.). The 10 hydroxycinnamic acids are identified in Achillea collina (Becker ex Rchb.) leaves (0.521±0.058%) and flowers (0.478±0.051%). Contents of the neo-chlorogenic acid (0.174±0.004%) and crypto-chlorogenic acid (0.088±0.007%) were the higest and P-coumaric acid yielded the lowest amount (0.010±0.001%) in study of flowers Achillea collina (Becker ex Rchb.). The study proved the presence of biologically and pharmacologically important flavonoids and hydroxycinnamic acids making the plant Achillea collina (Becker ex Rchb.) beneficial for the preparation of phytodrugs. A combination of two methods (TLC and HPLC) may be useful in a quality control as it used allow qualitative analysis of herbal raw material while maintaining accurate quantification of extract composition
Keywords: Achillea collina; polyphenolic compounds; Achillea millefolium ssp. Collina; Achillea L.